2020
DOI: 10.1002/slct.202001749
|View full text |Cite
|
Sign up to set email alerts
|

Peroxy‐Benzoic Acid Mediated Domino C[sp2] Hydroxylation /Annulation of Enaminones for the Synthesis of 3‐Hydroxy Chromones

Abstract: An efficient, facile, and clean synthesis of various 3‐hydroxy‐chromones (3‐hydroxy‐4H‐chromene‐4‐ones) via enamino ketone followed by cyclization using m‐chloroperbenzoic acid (MCPBA) has been described. The significant features of this method include simple method, high purity and excellent regio‐selectivity of the products. This is the first report for the two step one pot synthesis of 3‐hydroxyl chromone using MCPBA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…1 b In 2020, Behera and co-workers accomplished a simple and efficient method for the synthesis of 3-hydroxy chromones based on the C–H bond hydroxylation and chromone annulation of o -hydroxylphenyl enaminones initiated by m -chloroperbenzoic acid ( m -CPBA) (Scheme 14). 37 The results of control reactions showed that the electrophilic attack of peroxide oxygen to the CC bond of enaminone took place first, and then the annulation and deamination occurred in turns. According to the new and easily-handled protocol, diverse 3-hydroxy chromones were produced in 20–76% yields.…”
Section: Synthesis Of Six-membered O-heterocyclesmentioning
confidence: 99%
“…1 b In 2020, Behera and co-workers accomplished a simple and efficient method for the synthesis of 3-hydroxy chromones based on the C–H bond hydroxylation and chromone annulation of o -hydroxylphenyl enaminones initiated by m -chloroperbenzoic acid ( m -CPBA) (Scheme 14). 37 The results of control reactions showed that the electrophilic attack of peroxide oxygen to the CC bond of enaminone took place first, and then the annulation and deamination occurred in turns. According to the new and easily-handled protocol, diverse 3-hydroxy chromones were produced in 20–76% yields.…”
Section: Synthesis Of Six-membered O-heterocyclesmentioning
confidence: 99%
“…260 The synthesis of 3-hydroxy-4H-chromen-4-ones occurred through domino C(sp 2 )-H hydroxylation/annulation reaction of o-hydroxyaryl enaminones using m-chloroperbenzoic acid (MCPBA) in dichloromethane. 261 Domino C(sp 2 )-H sulfenylation/annulation reaction of o-hydroxyaryl enaminones with thiophenols promoted by aqueous HBr-DMSO system in chloroform at 100 °C, 262 and by KIO 3 in ethyl lactate at 60 °C263 furnished a series of 3-sulfenylated 4H-chromen-4-ones. Further derivatives were readily achieved via domino reaction of o-hydroxyaryl enaminones with sulfonyl hydrazines mediated by KIO 3 in DMF at 130 °C, 264 with DMSO mediated by propylphosphonic anhydride (T3P ® ) in THF at 100 °C, with aryl methylsulfoxide promoted by T3P ® in DMAc at 90 °C, 265 with diorganyl disulfides and arylsulfanyl hydrazides mediated by potassium iodate and glycerol at 100 °C( Scheme 35).…”
Section: Via O-hydroxyaryl Enaminone Formationmentioning
confidence: 99%
“…27 Using mCPBA as an oxidative reagent was used for 3-Hydroxy Chromone synthesis reported by R. Gudipati et al (Scheme 1, entry d). 28 The reported method involves use of stringent reaction conditions like micro-wave, elevated temperature and not used environnemental compatibility solvents. To overcome all these limitations, the development of new methodologies for the synthesis of chromon-4-one is still required.…”
Section: Introductionmentioning
confidence: 99%